IMPLEMENTASI PEMBELAJARAN MATEMATIKA REALISTIK BERBASIS ETNOMATEMATIKA - Asih Utami (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
The problems that often arise when researchers teach elementary mathematics learning courses to UPR PGSD students are the lack of student creativity in designing learning, the low student learning outcomes regarding mathematical concepts, and the learning activities they design are not suitable for class conditions. In this study, researchers applied an ethnomathematics-based realistic mathematics learning model as an example of an alternative learning that students could apply. This study aims to determine student activity in learning realistic mathematics based on ethnomathematics and to determine student creativity in designing elementary mathematics lessons. The subjects of this study were PGSD students who took elementary mathematics courses. This research is quantitative descriptive.The results showed that student activity in participating in ethnomathematics-based realistic mathematics learning was quite good with an average presentation of 91.43%. Student creativity in designing ethnomathematics-based mathematics learning has met several indicators of creativity assessment. Students are able to explore culture or handicrafts typical of Central Kalimantan to be used as media for learning mathematics. The media used include betang houses, saber, shields typical of Central Kalimantan, rattan handicrafts typical of Central Kalimantan and typical Central Kalimantan batik with a crisp stem pattern. Of the 5 study groups, 5 groups have fluency abilities, 4 groups have flexibility abilities and 2 groups have novelty abilities.